THE EFFECT OF FISH BONE POWDER WASTE AS A FINE AGGREGATE SUBSTITUTION IN ASPHALT CONCRETE WEARING COURSE PAVEMENT - TIAR WAHYUDI; YONAS PRIMA ARGA RUMBYARSO; BERMANDO MANGATUR SIAGIAN (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
Roads as transportation infrastructure play an important role in regional development and are used to transport basic necessities. Certain materials with specific durability are used for road construction, but damage can occur due to natural phenomena, excessive pressure, or material quality. This damage can endanger drivers and often causes accidents. The Bina Marga Road Maintenance Manual lists various types of damage, but this study only focuses on inspections to detect cracks. In Muara Angke, Central Jakarta, one ton of fish bone waste is produced every month from the fish cracker making process. This waste, which produces an unpleasant odor and contains BOD, COD, and TSS, pollutes the environment and makes the 400 m² industrial area unhealthy. Due to lack of skills and technology, local communities have not been able to process or utilize this fish bone waste effectively. The results of Marshall testing on the composition of AC-WC asphalt using fish bone powder waste with variations of fine aggregate substitution of 0%, 25%, and 50%, and asphalt content of 5%, 6%, and 7% did not meet the 2018 Bina Marga specifications for Stability, Void in Air, Marshall Quotient, and Void in Material values. The Marshall characteristics obtained from the mixture with fish bone powder waste are not comparable to the regular AC-WC mixture without waste. In addition, the VIM value for the mixture with 6% asphalt content and waste variations of 0%, 25%, and 50% also did not meet Bina Marga standards. However, all VMA and VFA levels still meet the asphalt and aggregate specification criteria according to Bina Marga 2018.